Distribution, source identification and ecological effects of aerosol dissolved nutrients in the Bohai Bay. (1st March 2023) - Cui, Xudong; Peng, Liying; Guo, Yu; Zhang, Guicheng; Liu, Haijiao; Wen, Yujian; Zhang, Guodong; Sun, Jun
Abstract: The atmospheric aerosols around the Bohai Bay are affected intensively by the surrounding industrial, shipping and other human activities. Although atmospheric dry deposition is an important way for nutrients to enter the Bohai Bay, few studies explore the distribution patterns, source and deposition fluxes of typical nutrients in aerosols and their impacts on the marine ecosystem. This paper explored the spatial-temporal distribution of typical aerosol nutrients in summer and autumn, and their source and ecological effects were illustrated further. The mean concentration of dissolved total phosphorus (DTP), dissolved total nitrogen (DTN), dissolved organic nitrogen (DON), dissolved inorganic nitrogen (DIN), ammonium (NH4 –N), nitrate (NO3 –N), nitrite (NO2 –N), silicate (SiO3 –Si), phosphate (PO4 –P), and dissolved organic phosphorus (DOP) were 31.22, 847.22, 288.19, 559.77, 288.19, 304.00, 253.65, 2.12, 15.74 and 15.48 nmol/m 3, respectively, while their fluxes were corresponding to 0.61, 8.36, 2.52, 4.90, 1.41, 2.49, 0.02, 0.04, 0.19 and 0.26 mmol/(m 2 month). Typical aerosol nutrient concentrations in autumn were mostly higher than those in summer, with high values occurring mainly in the central region. The potential sources of pollution were mainly concentrated in Shandong and Mongolia, and the sources of pollution were mainly agriculture, dust and industry. The large N:P and N:Si ratios in the dry deposition likely exacerbated Si and P limitation in the water column. These results provided the data basis for evaluating the pollution status and revealed that the dry deposition of aerosol nutrients should not be neglected by the ecological environment in the Bohai Bay. Graphical abstract: Image 1 Highlights: Inorganic nitrogen is one of the main pollutants in Bohai Bay's atmosphere. The high N/P ratio in Bohai Bay should, to some extent, be attributed to dry deposition. Pollutants in the atmosphere of Bohai Bay come mainly from the surrounding air masses. Aerosol N and P are impacted by the long-distance transportation of contaminants. Dry deposition can exacerbate phosphorus and silicon limitation in ocean surface waters.